(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Within the framework of this article, the types, and features of entrepreneurial activity in the Republic of Ingushetia are considered. The relevance of the work is because in order to make optimal decisions in order to make a profit, determine the main directions of business development, there is a need to understand the essence of entrepreneurial activity. The purpose of this work involves conducting a study of entrepreneurial activity with the definition of its essence and directions of development. Enterprises that could introduce new technologies in their activities achieve great success in obtaining a positive financial result and act as carriers of the country’s economy. For the effective functioning of a small business, it is of great importance to create certain legal conditions: a simplified and accelerated procedure for opening and registering enterprises, social protection of an entrepreneur, elimination of administrative barriers, improvement of tax and investment legislation.